2019
DOI: 10.3390/molecules24213974
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Physicochemical and FTIR Spectroscopic Properties of Bee Pollen Loads from Different Botanical Origin

Abstract: Bee pollen loads generally have a homogeneous and monospecific pollen content and assume a typical form and color, due to the typical bee foraging habits, thus having a typical composition related to the botanical origin. The present study aims to characterize bee pollen loads belonging to different botanical species using morphological, spectroscopic and color properties and to find relationships between these variables. IR spectra analysis allowed to have a reliable picture of the components present in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…Since the bee-pollen samples investigated in this study present a mixture of more than ten different pollen types, differentiation and classification based on chemical profile and distinct separation among the groups are difficult to perform, particularly when observing only one class of compounds and not combining several groups of parameters. Similar results were obtained based on NIR spectra of bee-pollen samples collected from twelve different Brazilian states [32], while Castiglioni et al suggest the possibility of using IR measurements for the classification of some Italian bee-pollen samples according their botanical origin [31]. The loading plots (Figure 3b-d…”
Section: Hptlc Fingerprint Of Phenolics In Bee-pollen Samplessupporting
confidence: 79%
See 1 more Smart Citation
“…Since the bee-pollen samples investigated in this study present a mixture of more than ten different pollen types, differentiation and classification based on chemical profile and distinct separation among the groups are difficult to perform, particularly when observing only one class of compounds and not combining several groups of parameters. Similar results were obtained based on NIR spectra of bee-pollen samples collected from twelve different Brazilian states [32], while Castiglioni et al suggest the possibility of using IR measurements for the classification of some Italian bee-pollen samples according their botanical origin [31]. The loading plots (Figure 3b-d…”
Section: Hptlc Fingerprint Of Phenolics In Bee-pollen Samplessupporting
confidence: 79%
“…Sample P23, which contains predominantly Robinia pollen, was positioned within the group that has predominantly Fabaceae pollen, suggesting that it has a similar phenolic content, which is in line with the fact that false locust (Robinia) belongs to the Fabaceae plant family. There are a certain number of scientific works that deal with determining the profile of a variety of chemical compounds in order to define the botanical origin of bee-pollen [7,31]. Since the bee-pollen samples investigated in this study present a mixture of more than ten different pollen types, differentiation and classification based on chemical profile and distinct separation among the groups are difficult to perform, particularly when observing only one class of compounds and not combining several groups of parameters.…”
Section: Hptlc Fingerprint Of Phenolics In Bee-pollen Samplesmentioning
confidence: 99%
“…The presence of these bands was expected, as previous studies reported that fresh pollen had moisture content between 7% and 30% [46]. In the region 3000-2850 cm −1 , the peaks that were identified in the spectra of the samples were assigned to symmetric and asymmetric stretching of C-H due to the presence of carbohydrates (mainly cellulose) and lipids [44,47]. For the pollen oil sample, the peaks in this region (2921.71 and 2852.41 cm −1 ) were more pronounced, which was expected considering the nature of this sample.…”
Section: Ft-ir Spectroscopysupporting
confidence: 62%
“…The spectra of these four samples were recorded in absorbance mode in the mid-infrared region and are presented in Figure 2. The wide absorption band, observed at 3289.64 cm −1 and 3288.90 cm −1 for crude pollen and the defatted pollen sample, and at 3328.11 cm −1 for pollen extract was attributed to stretching vibrations of O-H group and indicated the presence of water in the samples [44,45]. Moreover, the band at 1636.50 cm −1 (crude pollen) and 1634.77 cm −1 (defatted pollen) also corresponded to vibrations (bending) of the O-H group [45].…”
Section: Ft-ir Spectroscopymentioning
confidence: 95%
“…Known as an "all-round nutrition food," honeybee pollen has long been used to improve human nutrition and health (Zhao & Xu, 2013). It contains nutrients such as proteins, lipids, carbohydrates, vitamins, polyphenols, flavonoids, terpenes, carotenoids, and selenium (Castiglioni et al, 2019;Komosinska-Vassev, Olczyk, Kazmierczak, Mencner, & Olczyk, 2015). The antioxidant effect of honeybee pollen is mainly attributed to its flavonoid content; these compounds are effective in scavenging free radicals (Denisow & Denisow-Pietrzyk, 2016;Fatrcová-Šramková et al, 2013;Kocot, Kiełczykowska, Luchowska-Kocot, Kurzepa, & Musik, 2018;Zhang, Wang, Wang, & Li, 2015).…”
Section: Introductionmentioning
confidence: 99%